Prevalence Of Traditional Medications Through Native Floral Elements Among Tribal Communities Of Kachchh Arid Ecosystem, Gujarat, India - Joshi, Ekta B; Jain, BK; Joshi, Pankaj N; Soni, Hiren B (International Journal of Environment, 2013)
This communication deals with the documentation of 38 medicinal plant species used for indigenous medications by local villagers such as pastoralists (Maldharis) and farmers of Tapkeshwari Hill Range (THR), Bhuj Taluka, Kachchh District, Gujarat, India. Traditional knowledge on medicinally important plant species has been recorded from tribal communities through semi-questionnaire survey using an open-ended questionnaire datasheets. The response from the people interviewed clearly indicated that most of the villagers were fully or partially dependent on the forest produce for their primary healthcare requirements as well as for curing chronic or acute disorders and ailments. Plant parts such as bark, flowers, fruits, gum, latex, leaves, roots, seeds, and spadix, were found to be used for the cure of bronchitis, cold, cough, diabetes, diarrhea, dropsy, dysentery, earache, fever, fistula, gastric troubles, hypothermia, indigestion, piles, skin diseases, snake-bites, toothache, and ulcer. The most predominantly used 10 plant species in the area are Asparagus racemosus, Balanites aegyptiaca, Capparis cartilaginea, Cassia auriculata, Commiphora wightii, Enicostema axillare, Fagonia schweienfurthii, Maytenus emerginata, Tinospora cordifolia, and Tribulus terrestris. An enumeration of these 38 medicinal plant species is presented; each species is cited with correct scientific names, vernacular names, ailments treated for, mode of preparation and dosages. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 184-201 DOI: http://dx.doi.org/10.3126/ije.v2i1.9221